PELAKSANAAN KETERAMPILAN TATA KECANTIKAN DIPANTI SOSIAL BINA REMAJA KECAMATAN RUMBAI KOTA PEKANBARU - Pretty Rosy Mayrina Rosy Mayrina; Titi Maemunaty Titi Maemunaty; Widiastuti ' ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract. The purpose of this study is to investigate the implementation of the governance skills of beauty in Adolescent Development Social Institution Tassel District of Pekanbaru city of Riau Province. Implementation of beauty grammar skills are activities to realize the plan into action in order to achieve goals effectively and efficiently in order beauty skills. Divided into two, namely Tata beauty hair and skin beauty. Hairstyling includes work with hair that is alive and growing and consists of cleaning, cutting, perming, giving and removing color and nourishes hair. While the beauty of the skin include: facial care and make-up or make-up. Where the research was in Teenage Social Institution Development Rumbai Pekanbaru. The subjects were learners, tutors, managers and Adolescent Development in Social Institution Rumbai Pekanbaru. The study design was a naturalistic descriptive study with a qualitative approach that aims to describe systematically the facts or certain characteristics factually and accurately. Based on the description in chapter presenting research results, we can conclude that the course is Tata Beauty education and training programs that use competency based curriculum designed referring to the National Competence Indonesia (SKKNI) and adapted to the needs of the business and the beauty industry is the need for a training system which produces skilled learners, ready to work and be independent. Based on the results of research on the implementation of the governance skills of beauty in Adolescent Development Social Institution Tassel District of Pekanbaru city of Riau Province, viewed from two aspects namely hairstyling and skin care procedures, quite good. This means that the implementation of the governance skills of beauty in Social Institution Adolescent Development District of Pekanbaru city of Riau province Tassel has been running as it should.Keyword: beauty grammar skills.